New Urbanism and Educational Infrastructure Reform: Community School Redevelopment - Nadine, Alphonse (Journal of Progress in Civil Engineering, 2025)
The New Urbanism is one of the most influential planning movements since the late 20th century. The planning ideas and successful projects of New Urbanism are leading us to pursue the better living conditions. Under the influence of globalization, as the world’s fastest growing countries, the urban construction of India inevitably affected by the impact of new ideas. Meanwhile, during the process of construction emerged some urban problems. In the growing process of urbanization and suburbanization, the planning of Indian residential areas still remain the mode of function division and sprawl development. Therefore, the application of advanced new ideas to improve the planning of Indian residential area is well worth researching. This paper starts with issues about Indian contemporary residential community planning, and then confirms the research question. After that, this paper introduces the related concepts to define the objects of research. Through the theoretical study, extract the New Urbanism community design concepts. And then, analysis the design concepts, study three practical cases of New Urbanism residential community and two cases of Indian residential community, combining with the site observation, summarize the possibilities and opportunity of residential community planning in India. Meanwhile, proposed the planning ideas, which is on the basis of the research before, and design a proposal in Beijing to implement the research question. Finally, evaluate the proposal and clarify the research result, points out the problems that need further investigation.